Factors affecting postpartum bladder recovery: A literature review - Avissena Daffa Lintangseta; Efriyan Imantika; Hesti Yuningrum; Rodiani Rodiani (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Postpartum urinary dysfunction, particularly postpartum urinary retention (PPUR), is a common obstetric complication reflecting impaired bladder recovery in the early postpartum period. Postpartum urinary retention (PPUR) results from multifactorial mechanisms, including physiological changes during pregnancy, mechanical and intrapartum factors such as prolonged labor and obstetric interventions, and maternal characteristics. Purpose: to evaluates the pathophysiology of PPUR and factors influencing postpartum bladder recovery. Method: The literature search was carried out using several electronic databases, including PubMed, Scopus, ScienceDirect, and Google Scholar. Articles were searched using keywords adjusted to the research topic, including postpartum urinary retention, voiding dysfunction, postpartum bladder function, pregnancy, labor, and maternal and fetal factors on urinary retention. These keywords were combined using Boolean operators (“AND”, “OR”) to obtain relevant literature, either used individually or in combination Results:Evidence indicates that unrecognized or poorly managed PPUR may lead to bladder overdistension, detrusor dysfunction, recurrent urinary tract infections, and long-term voiding impairment, although most cases resolve with timely and appropriate management. Conclusion: A comprehensive understanding of these factors enables identification of high-risk women and implementation of effective bladder care strategies to reduce postpartum urological morbidity.